RANCANG BANGUN WHEELCHAIR LIFT ALAT BANTU PENYANDANG DISABILITAS MENGGUNAKAN SISTEM PNEUMATIK - Ekananta, Krisna Pramudya; Pambudi, Ardhenta Sigit; Wirawan, Willy Artha; Damayanti, Ajeng Tyas (Jurnal Transportasi, 2023)
Public service is an activity conducted to fulfill service needs in accordance with applicable regulations. Public services are intended for every user of the available service. The enhancement of public services is directed towards individuals with disabilities. A wheelchair lift is an assistive device used to facilitate individuals with disabilities who use wheelchairs to board and disembark from trains at low or moderate platforms. This device operates by lifting wheelchair users with disabilities without requiring manual assistance from human personnel. The design and construction of this device are developed by considering both mechanical and electrical aspects, ensuring it can be operated easily, reliably, efficiently, and capable of lifting a load of up to 117 kg. The utilization of this device can help reduce the risk of injuries for wheelchair-using individuals with disabilities when boarding and disembarking from trains. ABSTRAK Pelayanan publik merupakan kegiatan yang dilakukan dalam rangka pemenuhan kebutuhan pelayanan sesuai dengan peraturan yang berlaku. Pelayanan publik diperuntukan bagi setiap pengguna jasa pelayanan yang ada. Peningkatan pelayanan publik ditujukan untuk penyandang disabilitas. Wheelchair lift merupakan suatu alat bantu yang digunakan untuk memudahkan penyandang disabilitas pengguna kursi roda untuk naik turun kereta pada peron rendah maupun sedang. Alat ini bekerja dengan mengangkat penyandang disabilitas pengguna kursi roda tanpa harus diangkat manual oleh tenaga manusia. Rancang bangun alat ini dibuat dengan mempertimbangkan desain secara mekanikal maupun elektrikal sehingga dapat dioperasikan secara mudah, handal dan efisien serta mampu mengangkat beban 117 kg. Penggunaan alat ini dapat membantu mengurangi risiko cidera bagi penyandang disabilitas pengguna kursi roda pada saat naik turun kereta.